Kingdom of Swaziland : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper and Statistical Appendix for the Kingdom of Swaziland assesses the interaction of nonbank financial institutions (NBFIs) within the financial system and the real economy. Understanding the type of flows will help in designing policies to better manage capital flows and allow higher interest rate; and more attractive domestic investment opportunities could reduce outflows. The current global financial crisis provides useful lessons on the importance of an efficient regulatory and supervisory framework. However, regulation should be in line with economic structures and the stage of economic development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet